Studies on the Characteristics of Nanostructures Produced by Sparking Discharge Process in the Ambient Atmosphere for Air Filtration Application - Tewasin Kumpika; Stefan Ručman; Siwat Polin; Ekkapong Kantarak; Wattikon Sroila; Wiradej Thongsuwan; Arisara Panthawan; Panupong Sanmuangmoon; Niwat Jhuntama; Pisith Singjai (Crystals, 2021)
Among the various methods for the preparation of nanoparticles, a sparking process at atmospheric pressure is of interest because it is a simple method for producing nanoparticles ranging from a few nanometer-sized particles to agglomerated film structures. In this research, we studied the effects of metal electrode properties on nanoparticle sizes. The experiments were carried out by applying a high voltage to different metal sparkling tips. The transfer of energies from positive ions and electron bombardments induced the melting and vaporization of electrode metals. Based on this research, we have developed a model to describe the formation of a nanoparticle film on the substrate, placed under the sparking gap, and the nanostructure produced by metal vapor on the sparking electrodes. The model provides a realistic tool that can be used for the design of a large-scale coating and the application of nanoparticles developed by this process for the filtration of PM2.5 mask fabric by air.